Monetary and Fiscal Policy Design under EMU: A Dynamic Game Approach - Bas van Aarle; Jacob Engwerda; Joseph Plasmans; Arie Weeren (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper analyzes the problem of designing macroeconomic stabilization policies within the European Monetary Union (EMU) as a dynamic game between a centralized monetary authority, the European Central Bank (ECB), and national fiscal policy makers. Non-cooperative feedback Nash equilibrium and cooperative Nash bargaining solutions are determined under various assumptions about r ationing regimes in goods and labor markets and structural characteristics of the economies involved.
Keywords: 330